2021
DOI: 10.3389/pore.2021.594299
|View full text |Cite
|
Sign up to set email alerts
|

β-Elemene Triggers ROS-dependent Apoptosis in Glioblastoma Cells Through Suppressing STAT3 Signaling Pathway

Abstract: Glioblastoma is one of the most aggressive primary brain tumors with few treatment strategies. β-Elemene is a sesquiterpene known to have broad spectrum antitumor activity against various cancers. However, the signaling pathways involved in β-elemene induced apoptosis of glioblastoma cells remains poorly understood. In this study, we reported that β-elemene exhibited antiproliferative activity on U87 and SHG-44 cells, and induced cell death through induction of apoptosis. Incubation of these cells with β-eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…It can reduce tumor cell mitosis, induce tumor cell apoptosis, and inhibit tumor cell growth. 7 Our previous research found that it has a significant inhibitory effect on hHSFs, while it could reduce the expression of collagen fibers, and it was no cytotoxicity to normal fibroblasts. In general, the purpose of this article is to preliminarily explore the mechanism by which β-Elemene inhibits hHSFs activity and reduces collagen expression, which would provide a potential therapeutic drug for HS.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It can reduce tumor cell mitosis, induce tumor cell apoptosis, and inhibit tumor cell growth. 7 Our previous research found that it has a significant inhibitory effect on hHSFs, while it could reduce the expression of collagen fibers, and it was no cytotoxicity to normal fibroblasts. In general, the purpose of this article is to preliminarily explore the mechanism by which β-Elemene inhibits hHSFs activity and reduces collagen expression, which would provide a potential therapeutic drug for HS.…”
Section: Introductionmentioning
confidence: 95%
“…β‐Elemene is an anticancer active ingredient extracted from the ginger family plant Wenyujin, and it is a self‐dependent anticancer drug developed in our country. It can reduce tumor cell mitosis, induce tumor cell apoptosis, and inhibit tumor cell growth 7 . Our previous research found that it has a significant inhibitory effect on hHSFs, while it could reduce the expression of collagen fibers, and it was no cytotoxicity to normal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…10 b-Elemene is an ingredient extracted from the plant Wenyujin, which is derived from the ginger family and has been demonstrated to possess antineoplastic effects. 11 Guo et al 12 performed a study in which human hypertrophic scar fibroblasts were treated with b-Elemene for 24 hours and demonstrated the viability of these fibroblasts was decreased in a concentration-dependent manner. They were able to demonstrate that B-Elemene reduced collagen deposition and induced apoptosis through a stress, p53-like pathway.…”
Section: Other Dermatologic Usesmentioning
confidence: 99%
“…Hypertrophic scars occur as a result of impaired wound healing resulting in excessive tissue proliferation marked by increased fibroblasts and collagen 10 . β‐Elemene is an ingredient extracted from the plant Wenyujin, which is derived from the ginger family and has been demonstrated to possess anti‐neoplastic effects 11 . Guo et al 12 .…”
Section: Dermatologic Applicationsmentioning
confidence: 99%
“…The National Medical Products Administration of China has approved it for interventional and intracavitary chemotherapy and for treating cancerous pleural ascites. Furthermore, combining EEI with conventional radiotherapy or chemotherapy could improve their therapeutic effects (Jiang et al, 2017 ; Tong et al, 2020 ) against lung cancer (Chen et al, 2020 ), nasopharyngeal cancer, brain tumors (Liu S. et al, 2020 ), bone metastases, and others (Cai et al, 2021 ) while decreasing their adverse effects (Chen et al, 2020 ; Liu S. et al, 2020 ; Hashem et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%